Exploring the EEG representation of English listening comprehension under hypoxic conditions - Song, Yanhui; Yu, Ye (Frontiers in Neuroscience, 2025)
IntroductionUnderstanding the impact of hypoxic conditions on cognitive functions, including English listening comprehension, has garnered increasing attention due to its implications for high-altitude education and cognitive resilience. Traditional research in this domain has often relied on behavioral assessments or simple physiological metrics, which lack the granularity to capture the neural underpinnings of cognitive performance.MethodsThis study proposes a novel framework combining electroencephalography (EEG)-based neural decoding with the Dynamic Linguistic Enhancement Model (DLEM) to investigate English listening comprehension in hypoxic environments. DLEM integrates adaptive vocabulary acquisition, grammar contextualization, and cultural embedding, leveraging EEG to provide real-time, personalized insights into linguistic processing.ResultsThe experimental results demonstrate significant improvements in comprehension accuracy and cognitive load management, particularly under adaptive curriculum strategies outlined by the Contextual Augmented Learning Strategy (CALS).DiscussionBy bridging physiological responses with advanced educational methodologies, this work contributes a scalable and flexible approach to enhancing cognitive performance under hypoxia, aligning with the goals of understanding both physiological and pathological responses to high-altitude conditions.